E-Portfolio: value tensions encountered in documenting design case studies - Li, Qinyu; Tolmie, Peter; Weibert, Anne; Schorch, Maren; Müller, Claudia; Wulf, Volker (Ethics and Information Technology)
We present here the “e-Portfolio” concept, which aims to provide access to documented design case studies of design researchers’ practices. Our e-Portfolio has its origins in Grounded Design. We examine here how the e-Portfolio concept grew out of Grounded Design, the way it instantiates values, and how it contributes to our understanding of the ways in which shifting values in practice can have an impact beyond the individual.